2018
DOI: 10.3390/molecules23092164
|View full text |Cite
|
Sign up to set email alerts
|

Origanum vulgare L. Essential Oil as a Potential Anti-Acne Topical Nanoemulsion—In Vitro and In Vivo Study

Abstract: Antibiotics are often prescribed in acne treatment; however, Propionibacterium acnes and Staphylococcus epidermidis, the two of the major acne-associated bacteria, developed antibiotic resistance. Essential oils (EOs) present a natural, safe, efficacious and multifunctional alternative treatment. This study aimed to assess the potential anti-acne activity of selected seven EOs commonly used in Mediterranean folk medicine. Antimicrobial activity screening of these oils showed oregano to exhibit the strongest an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 37 publications
2
61
0
8
Order By: Relevance
“…Nevertheless, In addition to the aforementioned non-ionic surfactants, an interesting alternative is represented by the tri-block polymeric surfactants. Taleb et al reported the use of Pluronic F127 in the formulation of Origanum vulgare EO NE [74]. It is a surface active non-ionic ABA block copolymer having the following structural formula: (ethylene oxide)97(propylene oxide)69(ethylene oxide)97.…”
Section: Surfactantmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, In addition to the aforementioned non-ionic surfactants, an interesting alternative is represented by the tri-block polymeric surfactants. Taleb et al reported the use of Pluronic F127 in the formulation of Origanum vulgare EO NE [74]. It is a surface active non-ionic ABA block copolymer having the following structural formula: (ethylene oxide)97(propylene oxide)69(ethylene oxide)97.…”
Section: Surfactantmentioning
confidence: 99%
“…Although the stability of these systems is a fundamental aspect, the lack of such information in a remarkable number of publications has to be highlighted. In addition, when such information are present, they are reported only for short periods, such as 30 or 60 days [74,106,111], that cannot be considered sufficient to predict their behaviour over time ( Figure 4A). In this respect, some authors used predictive studies about the thermodynamic stability of MEs and NEs.…”
Section: Stabilitymentioning
confidence: 99%
“…The antibacterial activity on the main skin bacteria has been demonstrated by us in vitro while the one against propionibacterium by other researchers. 18 In addition, in a previous study, the essential oil of Origanum vulgare in nanoemulsion, tested in an acne animal mouse model, has been shown to be a potential anti-acne product. 18 The myrtle in previous studies has also shown in vitro a potential anti-acne activity associated with other plant extracts19 or antibiotics.…”
Section: Discussionmentioning
confidence: 96%
“…18 In addition, in a previous study, the essential oil of Origanum vulgare in nanoemulsion, tested in an acne animal mouse model, has been shown to be a potential anti-acne product. 18 The myrtle in previous studies has also shown in vitro a potential anti-acne activity associated with other plant extracts19 or antibiotics. 19,20 The anti-inflammatory action of the 2 essential oils has been demonstrated in vitro by other authors.…”
Section: Discussionmentioning
confidence: 96%
“…Over the years, the quest to solve the problems associated with drug delivery necessitated the development of various means of its delivery. This will foster patient compliance as well as improve the therapetic potentials as well as the bioavailability of the encapsulated drugs without necessarily increasing the concentration [4,5]. On this note, colloids have played a vital role in which series of emulsion have been formulated.…”
Section: Introductionmentioning
confidence: 99%